IPv6 Applicability in SCADA System Network - Hassaballa, Ahmed M.; ElHussein, , Abubakr E. M.; Agoub, Ali A. (Gezira Journal of Engineering and Applied Sciences, 2011)
The trend today is to build a secure fault tolerant Internet/Intranet connected distributed SCADA system networks using open and standard software/hardware. This paper made use of advances in Ethernet such as Fast/Gigabit Ethernet, micro-segmentation and full-duplex operation using switches, IPv6 enhanced features and TCP/IP to fulfill the real-time requirements for SCADA system network. OPNET Modeler simulator is used for modeling and simulating the network. The various measured delays showed that IPv6 introduction in such network introduces very small (negligible) delay and shows better performance on applying Quality of Service relative to IPv4. Also it is found that delays increase with increased transported packet size.